Drug‐induced cardiomyopathy: Characterization of a rat model by [18F]FDG/PET and [99mTc]MIBI/SPECT. Issue 4 (10th October 2020) - Houson, Hailey; Hedrick, Andria; Awasthi, Vibhudutta
Abstract: Background: Drug‐induced cardiomyopathy is a significant medical problem. Clinical diagnosis of myocardial injury is based on initial electrocardiogram, levels of circulating biomarkers, and perfusion imaging with single photon emission computed tomography (SPECT). Positron emission tomography (PET) is an alternative imaging modality that provides better resolution and sensitivity than SPECT, improves diagnostic accuracy, and allows therapeutic monitoring. The objective of this study was to assess the detection of drug‐induced cardiomyopathy by PET using 2‐deoxy‐2‐[ 18 F]fluoro‐D‐glucose (FDG) and compare it with the conventional SPECT technique with [ 99m Tc]‐Sestamibi (MIBI). Methods: Cardiomyopathy was induced in Sprague Dawley rats using high‐dose isoproterenol. Nuclear [ 18 F]FDG/PET and [ 99m Tc]MIBI/SPECT were performed before and after isoproterenol administration. [ 18 F]FDG (0.1 mCi, 200‐400 µL) and [ 99m Tc]MIBI (2 mCi, 200‐600 µL) were administered via the tail vein and imaging was performed 1 hour postinjection. Isoproterenol‐induced injury was confirmed by the plasma level of cardiac troponin and triphenyltetrazolium chloride (TTC) staining. Results: Isoproterenol administration resulted in an increase in circulating cardiac troponin I and showed histologic damage in the myocardium. Visually, preisoproterenol and postisoproterenol images showed alterations in cardiac accumulation of [ 18 F]FDG, but not of [ 99m Tc]MIBI. Image analysis revealed that myocardial uptake of [ 18 F]FDG reduced by 60% after isoproterenol treatment, whereas that of [ 99m Tc]MIBI decreased by 45%. Conclusion: We conclude that [ 18 F]FDG is a more sensitive radiotracer than [ 99m Tc]MIBI for imaging of drug‐induced cardiomyopathy. We theorize that isoproterenol‐induced cardiomyopathy impacts cellular metabolism more than perfusion, which results in more substantial changes in [ 18 F]FDG uptake than in [ 99m Tc]MIBI accumulation in cardiac tissue. Abstract : PET and SPECT nuclear images of cardiomyopathy.